Teachers’ Opinions on Teacher Resilience during the COVID-19 Pandemic - LEVENT, AHMET FARUK (My University, 2024)
The purpose of the study is to examine the teachers’ opinions on teacher resilience during the COVID-19 pandemic. The study employed a phenomenological design, implementing maximum variation sampling to select a participant group of 20 teachers from private schools in Istanbul and public schools in Erzurum's rural district, Hınıs. Semistructured interviews were conducted both in-person and virtually, after which descriptive and content analyses were undertaken utilizing the MAXQDA 2020 software, facilitating the identification of predominant themes and subthemes. Eight themes are surfaced from the study, encapsulating teachers' opinions on resilience, professional challenges, complications tied to distance education, environmental problems, factors contributing to resilience, leaving the profession, the COVID-19 pandemic's impact, along with suggestions for enhancing resilience. The study's findings indicate that teacher resilience during the COVID-19 pandemic is significantly affected by factors such as the lack of internet infrastructure, the lack of hardware, learning loss in students, absenteeism problems of students, physical distance, increase in workload, the lack of parental interest, the lack of support from the administration, and economic conditions. Conversely, professional dedication, professional development, positive attitude, administrative and parental support, collaboration among colleagues, and engaging in hobbies were identified as factors contributing to teacher resilience. Keywords: Resilience, teacher resilience, COVID-19 pandemic
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Social Sciences and Humanities; Education; Sosyal Bilimler (Soc); Sosyal Bilimler Genel; Eğitim Ve Eğitim Araştırması; Social Sciences (Soc); Social Sciences General; Education & Educational Research; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Resilience; teacher resilience; COVID-19 pandemic